Pengembangan Lembar Kerja Peserta Didik Berbasis Keterampilan Proses Sains pada Materi Larutan Eleketrolit dan Nonelektrolit - Nova Citra; Masriani Masriani; Lukman Hadi; Rody Putra Sarti; Maria Ulfah (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
This study aims to develop student worksheet based on science process skills and to determine the level of feasibility and teacher response to the developed student worksheet. The form of this research model is research and development (R&D) with reference to the ADDIE development model modified into ADD, namely Analysis, Design and Development. The subjects of this study were student worksheet and the responses of 3 chemistry teachers at SMA Kubu Raya. The data collection instrument used was the assessment sheet. the feasibility of the material, language, and graphics as well as the teacher's response questionnaire. The results of data processing show that the developed student worksheet is very suitable for use in learning electrolyte and non-electrolyte solutions in terms of the feasibility of material, language, and graphics with a percentage of 98.2% with a very feasible category. Based on the calculation of the teacher response questionnaire to the science process skills based student worksheet, it shows that the teacher response is very good with a percentage of 93%. Thus, science process skills based student worksheet is very suitable to be used in the learning process.